PELATIHAN PROMOSI UMKM NASI GORENG BAPER MELALUI INSTAGRAM - Wisnu Arief Fatulloh; Poppy Febriana; Ainur Rochmania; M Rigel Putra R (Jurnal Bina Bangsa Ekonomika, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the growth process and the economy in the country. In the digital era like today, the existence of internet access that is quite easy is a positive impact for MSME players. The emergence of online media creates information sharing about a product and can also provide convenience for consumers online. On Jl Siwalankerto, there is one MSME, namely baper fried rice, the problem faced by MSME players is the marketing system and product promotion still using conventional methods. In this community service program, it focuses on how to use and train Instagram as a promotional medium for this activity program using four stages such as Surveys, Interviews, Product Photo Taking, and Video Taking. The use of product catalog feed arrangements and promotional content creators will have an impact on the wider reach of the products issued by these MSMEs